PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BAHASA ARAB TINGKAT DASAR - Kanang Ulhadi; Aunurrahman Aunurrahman; Fadillah Fadillah (Universitas Tanjungpura, 2021)
AbstractThe research is aimed to develop multimendia learning languages Arabic levels of the base . Multimedia that development in the form vidio learning languages Arabic material family with the subject of research in the classroom of the elementary Islam Hidayaturrahman . Research is using the research development of R & D by using p rosedur development of research using the design development ADDIE which consists of five steps , namely , ( Analysis, Design , Development, Implementation and Evaluation ) . Data collection techniques used in this study are through questionnaires and utterance tests ( Qalam ) . The results of the design that was developed in the form of multimedia instructional shaped vidio appropriate analysis of needs , analysis of curriculum and analyzes the characteristics of students . Profile products multimedia resulting shaped vidio learning language arabic with the theme of the family were in the allotment pad grade one elementary Islam Hidayaturrahman . The effectiveness of multimedia that is developed based on the results of the posttest and pre e test that has been carried out distributed normal and with such results of the effectiveness of multimedia feasible and can be used as a source of learning. SaidKey : Multimedia Learning , Language Arabic